Hubungan antara Kecemasan dan Karakteristik Pasien di Instalasi Gawat Darurat Rumah Sakit di Sulawesi Tengah - Ferdy Lainsamputty; Metty Wuisang (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2022)
Background: Emergency patients have a very high chance of experiencing anxiey. Anxiety occurs due to several causes, from both from internal and external factors. Some demographic factors and patients characteristics may have potential relationship with anxiety. Objective: This study aimed to identify the relationship between patient characteristics and anxiety in the emergency department (ED). Methods: A descriptive correlational and cross-sectional design were employed. The population in this study were patients in the EDs. A total of 180 convenience samples were recruited from 2 general hospitals in Central Sulawesi Province of Indonesia. Data were collected using the Depression Anxiety Stress Scale 42 (DASS-42) questionnaire. Descriptive statistics and bivariate analysis (Mann-Whitney, Kruskal-Wallis, and Spearman Rank) were applied to identify the relationship between variables. Results: There was a very significant relationship between the type of payment and anxiety among patients in the ED (p0,01). No significant associations were found between anxiety and other patient characteristics (p0,05). Conclusion: Patients who used national insurance have a higher level of anxiety